Insoluble and soluble roasted walnut proteins retain antibody reactivity. (1st March 2016) - Downs, Melanie L.; Simpson, Angela; Custovic, Adnan; Semic-Jusufagic, Aida; Bartra, Joan; Fernandez-Rivas, Montserrat; Taylor, Steve L.; Baumert, Joseph L.; Mills, E.N. Clare
Highlights: Routine thermal processing may impact walnut allergen solubility and activity. Walnuts were roasted at 132 or 180 °C for 5, 10, or 20 min. Soluble protein decreased by 84% in the walnuts roasted at 180 °C for 20 min. Walnut proteins rendered insoluble still bound substantial levels of IgE. Aggregation and insolubility are critical effects of heat on food allergens. Abstract: Thermal processing techniques commonly used during food production have the potential to impact food allergens by inducing physical and/or chemical changes to the proteins. English walnuts ( Juglans regia ) are among the most commonly allergenic tree nuts, but little information is available regarding how walnut allergens respond to thermal processing. This study evaluated the effects of dry roasting (132 or 180 °C for 5, 10, or 20 min) on the solubility and immunoreactivity of walnut proteins. A dramatic decrease in walnut protein solubility was observed following dry roasting at 180 °C for 20 min. However, both the soluble and insoluble protein fractions from roasted walnuts maintained substantial amounts of IgG immunoreactivity (using anti-raw and anti-roasted walnut antisera), with similar patterns of reactivity observed for human IgE from walnut-allergic individuals. Thus, walnut proteins are relatively stable under certain thermal processing conditions, and IgE reactivity remains present even when insoluble aggregates are formed.